2013
DOI: 10.7740/kjcs.2013.58.4.336
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Genetic Diversity and Population Structure of Amaranth Accessions from South America Using 14 SSR Markers

Abstract: Amaranth (Amaranthus sp. L.) is an important group of plants that includes grain, vegetable, and ornamental types. Centers of diversity for Amaranths are Central and South America, India, and South East Asia, with secondary centers of diversity in West and East Africa. The present study was performed to determine the genetic diversity and population structure of 75 amaranth accessions: 65 from South America and 10 from South Asia as controls using 14 SSR markers. Ninety-nine alleles were detected at an average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 34 publications
1
9
1
Order By: Relevance
“…There is also genetic differentiation between grain and vegetable amaranth in this study, which has also been observed in many molecular markers studies, including AFLP [ 41 ], SSR [ 23 , 42 , 43 ] and GBS [ 15 ], although those studies incorporated far fewer A . tricolor accessions.…”
Section: Discussionsupporting
confidence: 78%
“…There is also genetic differentiation between grain and vegetable amaranth in this study, which has also been observed in many molecular markers studies, including AFLP [ 41 ], SSR [ 23 , 42 , 43 ] and GBS [ 15 ], although those studies incorporated far fewer A . tricolor accessions.…”
Section: Discussionsupporting
confidence: 78%
“…SSE is a non-governmental organization that works to preserve America's gardening heritage, so it would be important to determine the species through molecular means. In most studies [1,2,[22][23][24][25][26][27][28][29][30], molecular markers have been able to distinguish South American (A. caudatus, A. quitensis) from Central American (A. cruentus, A. hypochondriacus) species of the subgenus Amaranthus as well as outgroups from other subgenera. The other subgenera of the genus are subgenus Acnida (includes weedy amaranths such as A. palmeri and A. spinosus) and Albersia (includes wild and vegetable species such as A. tricolor and A. viridis).…”
Section: Discussionmentioning
confidence: 99%
“…The use of molecular markers such as Simple Sequence Repeat (SSR) or Single Nucleotide Polmorphism (SNP) seems better than morphological analysis for distinguishing species of grain amaranths [1,2,[22][23][24][25][26][27][28][29][30]. SSR markers in the study by Oo and Park [26] did find clear clustering pattern of geographically close accessions and related species but Suresh et al [1] did not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several single locus molecular markers have been used for amaranth characterization instead of morphological ones. These range from protein-based ones to DNA-based markers, including isozymes [ 20 , 21 , 22 ], RFLPs [ 23 ], SSRs [ 1 , 24 , 25 ] and SNPs [ 26 , 27 ]. Multi-locus markers have included RAPDs [ 28 , 29 , 30 ] and AFLPs [ 31 ].…”
Section: Introductionmentioning
confidence: 99%